(untitled) - Adams, Harold P (New York, 2007)
Richly illustrated with 500 illustrations, Principles of Cerebrovascular Disease offers solid clinical coverage of one of the three most prevalent neurologic diseases: stroke and stroke. Logically organized by the way patients present and with an emphasis on diagnosis and management, this resource answers every possible clinical question about stroke patients.
Keywords: Cerebrovascular disease,Cerebrovascular Accident,Cerebrovascular Disorders,Bệnh mạch máu não